Characterization of glucosinolates in 80 broccoli genotypes and different organs using UHPLC-Triple-TOF-MS method. (1st January 2021) - Li, Zhansheng; Zheng, Shuning; Liu, Yumei; Fang, Zhiyuan; Yang, Limei; Zhuang, Mu; Zhang, Yangyong; Lv, Honghao; Wang, Yong; Xu, Donghui
Highlights: UHPLC-Triple-TOF-MS method was demonstrated to be good for simultaneously detecting and quantifying glucosinolates. Twelve glucosinolate compounds were discovered in broccoli florets but varied among 80 genotypes. Nine glucosinolates and their regression relations were revealed by detection in developmental organs of broccoli. The principal component of glucobrassicin, neoglucobrassicin and glucoraphanin explained 60.53% of the total variance. Some mutant broccoli genotypes were discovered by analysis of gluconapin contents in different organs. Abstract: We aimed to characterize and quantify glucosinolate compounds and contents in broccoli, and a total of 80 genotypes and eight developmental organs were analyzed with UHPLC-Triple-TOF-MS. The method was validated in terms of performance, and the coefficients of determination (R 2 ) were 0.97 and 0.99 for glucoraphanin and gluconapin, respectively. In 80 genotypes, twelve glucosinolates were found in broccoli florets ranging from 0.467 to 57.156 µmol/g DW, with the highest glucosinolate content being approximately 122-fold higher than the lowest value. The principal component of glucobrassicin, neoglucobrassicin and glucoraphanin explained 60.53% of the total variance. There were positive correlations among hydroxyglucobrassicin, methoxyglucobrassicin, glucobrassicin, glucoerucin, gluconasturtiin, glucoraphanin, and glucotropaeolin ( P < 0.05). The root contained 43% of total glucosinolates in 80 genotypes, and glucoraphanin represented 29% of the total glucosinolate content in different organs. The mutant broccoli genotypes were found by analysis of gluconapin contents in different organs.